Magnitude and Determinants of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Household Transmission: A Longitudinal Cohort Study . (5th July 2022) - Kelly, J Daniel; Lu, Scott; Anglin, Khamal; Garcia-Knight, Miguel; Pineda-Ramirez, Jesus; Goldberg, Sarah A; Tassetto, Michel; Zhang, Amethyst; Donohue, Kevin; Davidson, Michelle C; Romero, Mariela; Diaz Sanchez, Ruth; et al.
Abstract: Background: Households have emerged as important venues for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission. Little is known, however, regarding the magnitude and determinants of household transmission in increasingly vaccinated populations. Methods: From September 2020 to January 2022, symptomatic nonhospitalized individuals with SARS-CoV-2 infection by RNA detection were identified within 5 days of symptom onset; all individuals resided with at least 1 other SARS-CoV-2–uninfected household member. These infected persons (cases) and their household members (contacts) were subsequently followed with questionnaire-based measurement and serial nasal specimen collection. The primary outcome was SARS-CoV-2 infection among contacts. Results: We evaluated 42 cases and their 74 household contacts. Among the contacts, 32 (43%) became infected, of whom 5 (16%) were asymptomatic; 81% of transmissions occurred by 5 days after the case's symptom onset. From 21 unvaccinated cases, 14-day cumulative incidence of SARS-CoV-2 infection among contacts was 18/40 (45% [95% confidence interval CI, 29%–62%]), most of whom were unvaccinated. From 21 vaccinated cases, 14-day cumulative incidence of SARS-CoV-2 infection was 14/34 (41% [95% CI, 25%–59%]) among all contacts and 12/29 (41% [95% CI, 24%–61%]) among vaccinated contacts. At least 1 comorbid condition among cases and 10 or more days of RNA detection in cases were associated with increased risk of infection among contacts. Conclusions: Among households including individuals with symptomatic SARS-CoV-2 infection, both vaccinated-to-vaccinated and unvaccinated-to-unvaccinated transmission of SARS-CoV-2 to household contacts was common. Because vaccination alone did not notably reduce risk of infection, household contacts will need to employ additional interventions to avoid infection. Abstract : Although vaccination prevents infection and severe illness, both vaccinated-to-vaccinated and unvaccinated-to-unvaccinated transmission of SARS-CoV-2 was common among households with symptomatic SARS-CoV-2 infection, particularly during the Delta and Omicron periods. Household contacts will need to employ additional interventions to avoid infection.